ANALISIS KINERJA KEUANGAN PT KRAKATAU STELL TBK (Study Empiris Pada Laporan Keuangan Periode 2016-2018) - M Suhendra; Kasmadi Kasmadi (Jurnal Riset Manajemen Indonesia, 2020)
This research was conducted at PT. Krakatau Steel Tbk in 2016 to 2018. This study aims to determine the performance of financial statements of PT Krakatau Steel Tbk as by Profitability ratio, Likuidity ratio, Activity ratio and solvency ratio and its deveploment during 3 years. The analysis tool used in this study is to use company’s Profitability Ratio including ROE and ROI. Liquidity Ratio through current ratio dan cash ratio. Activity ratio includes collection periods, inventory turn over, asset turn over and Solvency Ratio include own capital ratios to total asset by analyzing financial statements in 2016 until 2018. Which refers to ministerial regulation BUMN Numbers : KEP-100/MBU/2002. Based on the results of the discussion at PT. Krakatau Steel Tbk in 2016 until 2018 is on LESS HEALTHY predikety. Because the company suffered a considerable loss from 2016 to 2018.